Do capacity constraints trigger high growth for enterprises? - Alexander Coad; Clemens Domnick; Florian Flachenecker; Peter Harasztosi; Mario Lorenzo Janiri; Rozália Pál; Mercedes Teruel Carrizosa (European Investment Bank (EIB), 2021)
High-Growth Enterprises (HGEs) have a large economic impact, but are notoriously hard to predict. Previous research has linked high-growth episodes to the configuration of lumpy indivisible resources inside firms, such that high capacity utilisation levels might stimulate future growth. We theorize that firms reaching critically high capacity utilisation levels reach a 'trigger point' involving either broad-based investment in further growth, or shrinking back to previous levels. We analyse EIBIS survey data (matched to ORBIS) which features a question on time-varying capacity utilisation. Overcapacity is a transitory state. Firms enter into overcapacity after a period of rapid growth of sales and profits, and the years surrounding overcapacity have higher employment growth rates. Firms operating at overcapacity make incremental investments (e.g. capacity expansion, process improvements, and modern machinery) rather than investing in R&D and new product development. We find support for the 'fork in the road' hypothesis: for some firms, overcapacity is associated with launching into massive investments and subsequent sales growth, while for other firms, overcapacity is negatively related to both investments and sales growth.
Keywords: L25; 330; High-Growth Enterprises (HGEs); firm growth; investment; capacity utilisation; trigger points